Glycated Hemoglobin < 6.5% Is Associated With Uroseptic Shock in Diabetic Patients With Urinary Tract Infection - Lee, Yi-Chien; Chen, Tsung-Hsien; Hsiao, Meng-Chang; Hung, Peir-Haur; Tung, Shao-Hsien; Hsiao, Chih-Yen (Frontiers in Medicine, 2020)
This study aimed to compare the clinical characteristics and treatment outcomes of diabetic and non-diabetic individuals with urinary tract infection (UTI) and determine whether glycated hemoglobin (HbA1c) levels <6.5% leads to uroseptic shock in diabetic individuals. We retrospectively collected and analyzed the clinical data of 1,363 individuals with UTIs in Taiwan from January 2006 to January 2018. Of the 345 diabetic individuals, 61 (17.7%) developed uroseptic shock. Diabetic patients who developed uroseptic shock tended to be older and males and, had a history of congestive heart failure, urolithiasis, higher serum creatinine level during hospitalization, lower serum HbA1c level, bacteremia, and acute kidney injury. Backward stepwise multivariate logistic regression analysis showed that male gender (odds ratio [OR], 1.861; 95% confidence interval [CI], 1.009–3.433; P = 0.047), congestive heart failure (OR, 4.036; 95% CI, 1.542–10.565; P = 0.004), bacteremia (OR, 2.875; 95% CI, 1.539–5.370; P = 0.001), and HbA1c level <6.5% (OR, 2.923; 95% CI, 1.580–5.406; P = 0.001) were associated with an increased risk of developing uroseptic shock among diabetic patients during hospitalization due to UTI. HbA1c level <6.5% is independently associated with uroseptic shock in diabetic patients with UTI.